The economic costs of child maltreatment in UK. (14th September 2021) - Conti, Gabriella; Pizzo, Elena; Morris, Stephen; Melnychuk, Mariya
Abstract: Child maltreatment is a major public health problem with significant consequences for individual victims and for society. In this paper, we quantify for the first time the economic costs of fatal and nonfatal child maltreatment in the UK in relation to several short‐, medium‐, and long‐term outcomes ranging from physical and mental health problems to labor market outcomes and welfare use. We combine novel regression analysis of rich data from the National Child Development Study and the English Longitudinal Study of Aging with secondary evidence to produce an incidence‐based estimate of the lifetime costs of child maltreatment from a societal perspective. The discounted average lifetime incidence cost of nonfatal child maltreatment by a primary caregiver is estimated at £89, 390 (95% uncertainty interval £44, 896 to £145, 508); the largest contributors to this are costs from social care, short‐term health, and long‐term labor market outcomes. The discounted lifetime cost per death from child maltreatment is estimated at £940, 758, comprising health care and lost productivity costs. Our estimates provide the first comprehensive benchmark to quantify the costs of child maltreatment in the UK and the benefits of interventions aimed at reducing or preventing it.